DINAMIKA PSIKOLOGIS FEMALE BREADWINNERS DALAM KONSTRUKSI SOSIAL PATRIARKI BALI - Krisnawan, Putu Angga Ary; Tanaya, I Wayan Nathan Fanza (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
ABSTRACT The phenomenon of women becoming primary earners (female breadwinners) is increasingly evident in Indonesia, including in Bali. However, the rise of women’s economic roles is not always accompanied by adequate social acceptance, particularly within communities that continue to uphold patriarchal values. This article aims to analyze the psychological dynamics of female breadwinners within the context of Bali’s patriarchal social construction, including role strain, psychological conflict, social stigma, and adaptive strategies through social support and self-compassion. The method employed is a narrative literature review, examining relevant empirical and theoretical studies published between 2019 and 2025. The findings indicate that female breadwinners in Bali face multiple burdens, encompassing economic responsibilities, domestic duties, and customary obligations, which trigger work–family conflict, guilt, and emotional stress. Nevertheless, self-compassion, resilience, and social support serve as important protective factors that help women adapt and maintain their psychological well-being. This study highlights the importance of a multidimensional approach that considers psychological, social, and cultural aspects in empowering female breadwinners in Bali. ABSTRAK Fenomena perempuan sebagai pencari nafkah utama (female breadwinner) semakin meningkat di Indonesia, termasuk di Bali. Namun, peningkatan peran ekonomi perempuan tidak selalu diikuti oleh penerimaan sosial yang memadai, khususnya dalam masyarakat yang masih berpegang pada nilai patriarki. Artikel ini bertujuan untuk menganalisis dinamika psikologis female breadwinner dalam konteks konstruksi sosial patriarki Bali, mencakup tekanan peran, konflik psikologis, stigma sosial, serta strategi adaptasi melalui dukungan sosial dan self-compassion. Metode yang digunakan adalah kajian literatur naratif dengan menganalisis penelitian empiris dan teoritis yang relevan pada rentang tahun 2019–2025. Hasil kajian menunjukkan bahwa perempuan breadwinner di Bali menghadapi beban ganda berupa tanggung jawab ekonomi, domestik, dan kewajiban adat, yang memicu work–family conflict, rasa bersalah, dan stres emosional. Meskipun demikian, self-compassion, resiliensi, dan dukungan sosial terbukti menjadi faktor protektif penting yang membantu perempuan beradaptasi dan mempertahankan kesejahteraan psikologisnya. Studi ini menegaskan pentingnya pendekatan multidimensional yang mempertimbangkan aspek psikologis, sosial, dan budaya dalam pemberdayaan female breadwinner di Bali.